2022
DOI: 10.1161/circheartfailure.121.009281
|View full text |Cite
|
Sign up to set email alerts
|

Catheter Ablation of Atrial Fibrillation in Patients With Heart Failure and Preserved Ejection Fraction

Abstract: Background: Coexistence of atrial fibrillation (AF) and heart failure with preserved ejection fraction (HFpEF) is common, affecting morbidity and prognosis. This study evaluates outcome after cryoballoon ablation for AF in HFpEF compared with patients without heart failure. Methods: A total of 102 AF patients with left ventricular ejection fraction ≥50% undergoing cryoballoon ablation were prospectively enrolled. Baseline evaluation included echocardiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 31 publications
0
19
0
Order By: Relevance
“…In summary, Zylla et al 6 should be commended on a well-conducted hypothesis-generating study that highlights the importance of identifying HFpEF in patients with symptomatic AF. The lack of observed benefit for AF ablation does not exclude AF as a potential therapeutic target in some patients with HFpEF.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In summary, Zylla et al 6 should be commended on a well-conducted hypothesis-generating study that highlights the importance of identifying HFpEF in patients with symptomatic AF. The lack of observed benefit for AF ablation does not exclude AF as a potential therapeutic target in some patients with HFpEF.…”
Section: Discussionmentioning
confidence: 99%
“…Zylla et al 6 have reported what is often suspected: that AF may be a marker of worse HFpEF in patients with both conditions and targeting AF may not have a meaningful impact in this population. Yet they stand alone among published observational studies which mostly report positive effects of AF ablation on symptoms, QOL, LV diastolic dysfunction, and even reduced HF hospitalization rates among patients with HFpEF.…”
Section: See Article By Zylla Et Almentioning
confidence: 99%
See 2 more Smart Citations
“…The limited diagnosis of HFpEF is highlighted by the fact that only 4.5% of the cohort had HFpEF, inconsistent with previous studies utilising noninvasive HFpEF scoring tools or invasive hemodynamic assessment, which have shown the prevalence of HFpEF in AF ablation cohorts to be considerably higher. 6 , 7 HFpEF has likely therefore been underdiagnosed in this study, and potentially limited to a sicker cohort. As a result, the rate of complications may not reflect that of an HFpEF cohort diagnosed more stringently.…”
mentioning
confidence: 93%